Hubungan Tingkat Pengetahuan Keluarga Dengan Kekambuhan Pada Pasien Gangguan Jiwa di Wilayah Kerja Puskesmas Sukamerang - Hasbi Taobah Ramdani; Wahyudin Wahyudin; Ade Intan Banatu Rahmi (Jurnal Medika Cendikia, 2014)
The mental disorder that can attack all usia.Dari year to people with mental disorders tend to increase. Knowledge of the family in caring for mental patients at home can affect the incidence of recurrence. The general objective of this study was to determine the relationship between the level of knowledge of families with recurrence of mental patients in Puskesmas Sukamerang District of Kersamanah 2014. The research design used in this study is a correlation study with cross sectional approach. The population in this study were relatives of patients in Puskesmas Sukamerang totaling 130 people. using random sampling technique, the sample in this study are as many as 43 people. The results showed that based on the statistical test, which is obtained by P-value = 0.003. Since the P-value ≤ α (0.05), so it can be concluded that there is a significant relationship between knowledge with the incidence of recurrence